MOSQUE-BASED COMMUNITY EMPOWERMENT : Case Study : Billionaire Muslim Mosque at Cinangneng, Tenjoloyo, Bogor, West Java - Giyanti, Ummu Ahya; Siti Aisah (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2024)
Research Objective: To determine the process of implementing mosque-based community empowerment at Masjid Muslim Billionaire Cinangneng Tenjolaya, Bogor Research Methods: Qualitative. Research Results: This research shows that Muslim Billionaire Mosque has carried out community empowerment programs through three stages. First, stage of awareness and formation, programs carried out are Pasar Bahagia, Majelis Bahagia, Pondok CEO Scholarship Program, and Gerakan Gizi Santri; stages of transformation of knowledge and skills, programs carried out are Pondok CEO and Memorization is Easy; and the stage of improving intellectual abilities and skills, programs be conducted are Pondok CEO and Baitul Muamalah program. Conclusion: The results of the empowerment carried out by the Masjid Muslim Billionaire stated that with the existence of a mosque-based community empowerment program carried out by the managements of the Masjid Muslim Billionaire, so the mosque congregation, the community around the mosque, and also Muslims in generally could feel the positive impact of this activity. The activities carried out are capable of being independent, empowering, and can improve people's understanding of religion for the better Keyword: empowerment, community, mosque